2020
DOI: 10.1186/s13662-020-03041-w
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo almost periodic synchronization of Clifford-valued fuzzy cellular neural networks with time-varying delays on time scales

Abstract: At present, the research on discrete-time Clifford-valued neural networks is rarely reported. However, the discrete-time neural networks are an important part of the neural network theory. Because the time scale theory can unify the study of discrete- and continuous-time problems, it is not necessary to separately study continuous- and discrete-time systems. Therefore, to simultaneously study the pseudo almost periodic oscillation and synchronization of continuous- and discrete-time Clifford-valued neural netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Until now, FCNN is still a hot topic. Many researchers have revealed that FCNN has a wide range of applications in the field of intelligent computing(see Cui et al, 2021; Duan et al, 2019a; Li and Shen, 2020b; Wang, 2018). Therefore, studying the dynamical behavior of FCNN has important theoretical and practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, FCNN is still a hot topic. Many researchers have revealed that FCNN has a wide range of applications in the field of intelligent computing(see Cui et al, 2021; Duan et al, 2019a; Li and Shen, 2020b; Wang, 2018). Therefore, studying the dynamical behavior of FCNN has important theoretical and practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…The usual ways of studying the stability of RVNN and CVNN cannot be directly applied to research the same issues of QNN. To overcome the challenge, decomposition approaches are proposed, which splits the considered QVNN into equivalent four RVNNs or two CVNNs [11][12][13][14][15][16][17][18]. However, the decomposition methods have observable limitations: (i) they require the activation functions to be decomposable; yet, not all quaternion functions are decomposable; (ii) the decomposition methods often induce a bulky computing cost.…”
Section: Introductionmentioning
confidence: 99%
“…The Clifford-valued neural network is a generalization of a real-valued neural network, complex-valued neural network, and quaternion-valued neural network, and has been shown superior to a real-valued neural network [1,2]. Because the multiplication of Clifford algebra does not meet the commutative law, there are few results on the dynamics of Clifford-valued neural networks [3][4][5][6][7][8][9][10][11]. Many existing results are obtained by decomposing a Clifford-valued system into a real-value system [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many existing results are obtained by decomposing a Clifford-valued system into a real-value system [3][4][5][6]. Therefore, it is a meaningful and challenging work to study the dynamics of Clifford-valued systems via a direct method; that is, without decomposing Clifford-valued systems into real-valued systems [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%